Phase structure of (2+1)-flavor QCD and the magnetic equation of state - Gao, Fei; Pawlowski, Jan M. (Physical review, 2022)
We determine the chiral phase structure of (2+1)-flavor QCD in dependence of temperature and the light flavor quark mass with Dyson-Schwinger equations. Specifically, we compute the renormalized chiral condensate and its susceptibility. The latter is used to determine the (pseudo)critical temperature for general light current quark masses. In the chiral limit we obtain a critical temperature of about 141 MeV. This result is in quantitative agreement with recent functional renormalization group results in QCD and is compatible with the respective lattice results. We also compute the order parameter potential of the light chiral condensate, map out the regime in the phase diagram which exhibits quasi-massless modes, and discuss the respective chiral dynamics.